2021
DOI: 10.1038/s41467-021-22011-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of artificial light at night on diurnal plant-pollinator interactions

Abstract: Artificial light at night has rapidly spread around the globe over the last decades. Evidence is increasing that it has adverse effects on the behavior, physiology, and survival of animals and plants with consequences for species interactions and ecosystem functioning. For example, artificial light at night disrupts plant-pollinator interactions at night and this can have consequences for the plant reproductive output. By experimentally illuminating natural plant-pollinator communities during the night using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…In addition to direct effects, we expected that ALAN might also have indirect effects on alien plant invasion via other trophic levels. This is because alien plants often attract different numbers and types of insects than native plants do 35,36,38 , and ALAN could also modify plant-insect interactions 7,9,31,32 . Our study, however, found no evidence that insect exclusion mediated the effects of ALAN on alien and native plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to direct effects, we expected that ALAN might also have indirect effects on alien plant invasion via other trophic levels. This is because alien plants often attract different numbers and types of insects than native plants do 35,36,38 , and ALAN could also modify plant-insect interactions 7,9,31,32 . Our study, however, found no evidence that insect exclusion mediated the effects of ALAN on alien and native plants.…”
Section: Discussionmentioning
confidence: 99%
“…Light pollution due to artificial light at night (ALAN) has increased dramatically in the last century, and has altered the natural night-time environment in large areas of the Earth 1,2 . As a consequence, ecological impacts of ALAN have become an important focus for global change research in recent years [3][4][5][6][7][8][9] . To date, most research on the impact of ALAN has focused on the behavior, physiology, and life history of animals [10][11][12][13] , and only a few studies have focused on plants 6,12,14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global environmental pressures threaten biodiversity directly through changes in species' physiology and behavior, and indirectly through interactions between impacted species and other species within ecological communities (Tylianakis et al, 2008). To date only a few studies have quantified indirect effects of ALAN caused by altered species interactions within (Knop et al, 2017;Giavi et al, 2020Giavi et al, , 2021, or across trophic levels (Bennie et al, 2018;Manfrin et al, 2018;Maggi et al, 2020), and we are far from being able to predict where indirect effects occur and their likely importance for the wider ecosystem.…”
Section: Consequences For Biodiversitymentioning
confidence: 99%